Murder through the English post - Ellicott, Jessica (Ellicott, Jessica. Beryl and Edwina mystery., 2022)
"A series of anonymous accusations sent via post have set friend against friend and neighbor against neighbor. In her new position as magistrate, Edwina has already had to settle one dispute that led to fisticuffs. Even Beryl has received a poison pen letter, and while she finds its message preposterous and laughable, others are taking the missives to heart. Their headstrong housekeeper Beddoes is ready to resign and one villager has attempted to take her own life. The disruption of the peace goes far beyond malicious mischief when another villager is murdered. Now it's up to the intrepid sleuths to read between the lines and narrow down the suspects to identify the lethal letter writer and ensure that justice is delivered"--